2017
DOI: 10.3989/gya.1057162
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasound on olive oil extraction and optimization of ultrasound-assisted extraction of extra virgin olive oil by response surface methodology (RSM)

Abstract: SUMMARY:In this study, the effects of different extraction parameters including ultrasound time, temperature and malaxation time on olive oil quality were investigated. The extraction variables ultrasound initial temperature (20-50 °C), ultrasound time (2-10 min) and malaxation time (30-50 min) were studied to obtain ideal conditions of ultrasonic treatment on the olive paste for obtaining of a greater yield in the extraction of oil, while maintaining a maximum level of commercial quality. To evaluate the leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 29 publications
2
44
0
1
Order By: Relevance
“…These results were in good agreement with the predicted values under the optimum working condition. Therefore, the acidity value of olive oil and yield for any combination of ultrasound time, ultrasound temperature and malaxation time could be accurately predictor by the regression models obtained by RSM [10]. In the 2005-2006 season, the estimated extraction yield, acidity and peroxide index of the 3.2 MI olive samples showed that the experimental data were consistent with the model for all three dependent variables [32].…”
Section: Validation Of the Modelsupporting
confidence: 61%
See 3 more Smart Citations
“…These results were in good agreement with the predicted values under the optimum working condition. Therefore, the acidity value of olive oil and yield for any combination of ultrasound time, ultrasound temperature and malaxation time could be accurately predictor by the regression models obtained by RSM [10]. In the 2005-2006 season, the estimated extraction yield, acidity and peroxide index of the 3.2 MI olive samples showed that the experimental data were consistent with the model for all three dependent variables [32].…”
Section: Validation Of the Modelsupporting
confidence: 61%
“…Using Response Surface Method in the extraction studies has been of interest to many researchers in recent years [10,13,14]. The steps that must be followed in order to apply this method correctly are shown in Figure 1.…”
Section: Rsm Application In Optimization Of Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of high frequency ultrasound standing waves, also known as megasound (MS), to the olive paste has also been tested industrially as a process intervention post malaxation to enhance olive oil recovery . Extractability improvements of up to 1.7% were seen after testing the technology at 300 kg h −1 .…”
Section: Introductionmentioning
confidence: 99%